Effect of different heat transfer fluids on discharging performance of phase change material included cylindrical container during forced convection - Selimefendigil, Fatih; Sirin, Ceylin; Öztop, Hakan Fehmi (Journal of Central South Univ, 2021)
In the present work, effects of various heat transfer fluids on the discharging performance of a phase change material (PCM) included cylindrical container are numerically assessed during forced convection. The heat transfer fluid air, hydrogen, water and nanofluid with alumina particles are used and the the geometric variation of the PCM embedded region is also considered. The finite element method is used as the solver. Dynamic features of heat exchange with various phases are explored for different heat transfer fluid types, Reynolds number (between 100 and 300) and PCM embedded region geometric variation (h(x) between 0.01d(1) and 0.65d(1), h(y) between 0.1h(1) and 0.4h(1)). It is observed that discharging time is significantly influenced by the heat transfer fluid type while full phase transition time for air is obtained as more than 10 times when hydrogen is utilized as heat transfer fluid. The best performance is achieved with nanofluid. When the PCM integrated region size is reduced, discharging time is generally reduced while due to the form of the geometry, vortex formation is established in the PCM region. This results in performance degeneration at the highest radius and height of the inner cylinder. Discharging time increases by about 12% when radius of the inner cylinder is increased from h(x)=0.35d(1) to h(x)=0.45d(1). Dynamic features of PCM temperature and liquid fraction are affected with Reynolds number while discharging time is reduced by about 48% when configurations with the lowest and highest Reynolds number are compared.
Keywords: heat transfer fluid; hydrogen; phase change material; finite element method; container shape